Chemical composition and antibacterial activity of Piper lenticellosum C.D.C essential oil collected in Ecuador - Morocho Zaragocin, S. (2016)
The essential oil of the leaves and spikes of Piper lenticellosum C. DC. (Piperaceae) was isolated by hydrodistillation and analyzed by GC/MS. A yield of 2.06 % was obtained. Twenty eight components were identified by comparison of their mass spectra with Wiley GC-MS library data and the retention indices (RI) calculated for every compounds. The major constituents were Piperitone (33.97 %), 1,8 cineole (11.92 %), limonene (11.07 %), safrole (8.18 %) and alpha-pinene (4.49 %). Antibacterial activity of the essential oil was evaluated against five important human pathogenic bacterial strains using the disk diffusion agar method. The results showed at moderate activity against Staphylococcus aureus ATCC (25923), Escherichia coli ATCC (25922) and Klebsiella pneumoniae ATCC (233357) with minimal inhibitory concentration (MIC) values of 100, 200 y 300 L/mL, respectively. According to the literature consulted, this is the first report on chemical composition and antibacterial activity of the essential oil of Piper lenticelosum C. DC. from Ecuador.